From Rural to Urban Living. A survey among internal migrants from Sami core areas to cities in Norway - Melhus, Marita; Eliassen, Bent Martin; Broderstad, Ann Ragnhild (2021)
Poster presentation at the online conference Arctic Frontiers 2021, 01.02.21 - 04.02.21. https://www.arcticfrontiers.com/arctic-frontiers-2021-building-bridges-summary-and-reports/.